Pengembangan Media Jarimatika Flanel berbasis model 4D untuk stimulasi perkembangan kognitif anak usia dini di sekolah PAUD BA Restu 2 Kota Malang - Amalya, Meyfa Nur Alfu Laila (Maliki Interdisciplinary Journal, 2026)
This study aims to develop the Jarimatika Flanel learning media based on the 4D development model (Define, Design, Develop, Disseminate) to stimulate the cognitive development of early childhood at PAUD BA Restu 2, Malang City. The media is designed to assist children aged 4–6 in understanding number concepts and basic arithmetic operations in a concrete, visual, and kinesthetic way. The development process involved observation, interviews, expert validation, and limited trials which showed that Jarimatika Flanel effectively improves children's abilities in recognizing numbers, counting, and solving simple problems. The media also positively impacts fine motor development and children's learning enthusiasm. The findings recommend Jarimatika Flanel as an innovative and applicable educational tool in early childhood education.